Peramalan Indeks Harga Prulink Rupiah Equity Fund Dengan Metode Exponential Moving Average - Mahadewa, Agung; Aryawan, Made Gitra; Prasetyo Utomo, Pradita Eko (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2018)
Company that has the added investment products with protection products, from a variety of investment products offered, product PRUlink Rupiah Equity Fund is the most desirable, the product has a high volatility compared to other products. Because it is a customer who is also an investor in this case, often feel disadvantaged by the insurer at the time of withdrawal own funds, it is caused by a lack of knowledge to know the price index next period Alleged right is the main information needed by investors to determine the next strategy in investing, One is the method of Exponential Moving Average. This method is a method of time series are used to predict the future by using historical data. Assigning weights to involve periods, so the longer the period that we use, the smaller the final value weighting we use With the abundance of available data, the construction of a system that utilizes past data, in other words, try using a time series model time series of the past to predict, the system will be useful to assist investors in predicting the allegations of the value of equity funds in the future so as to determine the appropriate strategy for investment.